2018
DOI: 10.1111/jdv.15120
|View full text |Cite
|
Sign up to set email alerts
|

CD34 stromal expression is inversely proportional to smooth muscle actin expression and extent of morphea

Abstract: Mutually exclusive staining patterns of CD34 stromal and SMA stains suggest a phenotypic change of CD34+ DDCs into SMA+ myofibroblasts with increasing disease extent and fibrosis in morphea. Degree of loss of CD34+ DDCs can be a useful marker in predicting the extent and severity of morphea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Although generalized morphea and eosinophilic fasciitis are believed to be different diseases, they are similar in presentation and are sometimes difficult to differentiate from each other. Previous studies showed that CD34 expression decreased or disappeared in the lesional skin of scleroderma, including morphea [11], which is inversely related with the extent of morphea [12]. CD34 is a marker of dermal dendritic cells and expression of CD34 and type I collagen suggest fibrocytes in the peripheral circulation.…”
Section: Figures 2 A) a Biopsy Specimen From The Forearm Shows Fibrosis Of Deep Dermis And Subcutis And Thickened Muscle Fascia With Inflmentioning
confidence: 96%
“…Although generalized morphea and eosinophilic fasciitis are believed to be different diseases, they are similar in presentation and are sometimes difficult to differentiate from each other. Previous studies showed that CD34 expression decreased or disappeared in the lesional skin of scleroderma, including morphea [11], which is inversely related with the extent of morphea [12]. CD34 is a marker of dermal dendritic cells and expression of CD34 and type I collagen suggest fibrocytes in the peripheral circulation.…”
Section: Figures 2 A) a Biopsy Specimen From The Forearm Shows Fibrosis Of Deep Dermis And Subcutis And Thickened Muscle Fascia With Inflmentioning
confidence: 96%
“…Another current area of study into potential histologic measures of morphea is regarding the altered distribution of dermal dendritic cells and vascular abnormalities that have been reported to relate the pathogenesis of morphea. Studies of morphea skin indicate that patients with morphea demonstrate a phenotypic change of CD34+ dendritic cells into SMA+ myofibroblasts with increasing disease extent and fibrosis (92). The degree of loss of CD34+ dendritic cells has been found to correlate with relative degrees of inflammation and sclerosis, and thus this has been proposed as a useful marker in predicting morphea severity and extent (92,93).…”
Section: Histologic Markersmentioning
confidence: 99%
“…Studies of morphea skin indicate that patients with morphea demonstrate a phenotypic change of CD34+ dendritic cells into SMA+ myofibroblasts with increasing disease extent and fibrosis (92). The degree of loss of CD34+ dendritic cells has been found to correlate with relative degrees of inflammation and sclerosis, and thus this has been proposed as a useful marker in predicting morphea severity and extent (92,93). Further studies have shown that treatments such as pulsed dye laser and UVA1 phototherapy are effective in improving indurated skin and reducing disease activity in morphea, and are also associated with an increase in the number of CD34+ cells (94,95).…”
Section: Histologic Markersmentioning
confidence: 99%
“…18 In differentiation from other conditions with a similar pattern, immunohistochemistry with CD34 is often helpful as it shows a variable loss of CD34(þ) dermal dendritic cells. 19,20 Recently, an increased interstitial expression of FXIIIa, SMA and VCAM-1 suggesting a phenotypic change of CD34þ dendritic cells into SMA þ myofibroblasts has been observed. 20 Intraepidermal lymphocytes are usually absent in morphea with the exception of manifestations that show overlapping features with lichen sclerosus.…”
Section: Morpheamentioning
confidence: 99%
“…19,20 Recently, an increased interstitial expression of FXIIIa, SMA and VCAM-1 suggesting a phenotypic change of CD34þ dendritic cells into SMA þ myofibroblasts has been observed. 20 Intraepidermal lymphocytes are usually absent in morphea with the exception of manifestations that show overlapping features with lichen sclerosus. In such cases, however, the hyalinizing sclerosis in the superficial is highly characteristic.…”
Section: Morpheamentioning
confidence: 99%